Manajemen Resiko pada Mebel Jepara Waidoko - Maria Gustiana Wanda; Yonitha Regi; Fransiska Nona Fani; Maria Noni (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
The furniture industry is a strategic sector in the regional economy, including in Sikka Regency, East Nusa Tenggara, where the JeparaWaidoko furniture business owned by Mr. Agus Komarudin has been operating since 2010. In running its business, Mebel JeparaWaidoko faces various operational risks that have the potential to disrupt production continuity, employee safety, and financial stability. This study aims to comprehensively analyze the risk management process at this business, including risk identification, risk analysis and assessment, evaluation and prioritization, and implementation and monitoring of risk controls. The method used was descriptive qualitative, using in-depth interviews with the business owner and field observations. The study identified three main risks: the risk of flooding, the risk of workplace accidents due to the use of production machinery, and the risk of rising raw material prices. All three are categorized as high-priority risks requiring planned and systematic management. These findings indicate that risk management practices at Mebel JeparaWaidoko remain informal and intuitive, despite the implementation of simple control measures. This study recommends formalizing an ISO 31000-based risk management system, improving occupational health and safety programs, and diversifying raw material suppliers as medium-term strategic steps